The Clinical Characteristics of Different SARS-COV-2 Variants in South Kalimantan - Haryati, Haryati; Rahmawaty, Desi (Universitas Muhammadiyah Yogyakarta, 2023)
COVID-19 has numerous variations as a result of ongoing mutations. Presumably, each variant has its particular clinical characteristic. We present three cases of COVID-19 patients, each with a Non-VOC, delta variant, and probable omicron variant with equal severity and few comorbidities for uniform comparison. All three cases had common COVID-19 symptoms. However, anosmia or ageusia was not found in the probable Omicron case, and the onset was shorter. Infiltrates in chest X-rays were found in all three cases. Laboratory examination showed altered inflammatory markers, transaminitis, and electrolyte imbalance. The standard therapy was given to all patients. However, additional therapies, tocilizumab, IVIG, and plasma convalescent, were given only to Non-VOC and delta variants cases. Non-VOC and delta cases were discharged for self-isolation in 11 and 15 days of treatment. Meanwhile, in the probable Omicron variant, the patient was discharged by his will after being treated for eight days.